On the clouds and ammonia in Jupiter's upper troposphere from Juno JIRAM reflectivity observations. Issue 4 (15th March 2021) - Grassi, Davide; Mura, A; Sindoni, G; Adriani, A; Atreya, S K; Filacchione, G; Fletcher, L N; Lunine, J I; Moriconi, M L; Noschese, R; Orton, G S; Plainaki, C; et al.
ABSTRACT: We analyse spectra measured by the Jovian Infrared Auroral Mapper (JIRAM, a payload element of the NASA Juno mission) in the 3150–4910 cm −1 (2.0–3.2 μ m) range during the perijiove passage of 2016 August. Despite modelling uncertainties, the quality and the relative uniformity of the data set allow us to determine several parameters characterizing the Jupiter's upper troposphere in the latitude range of 35°S–30°N. Ammonia relative humidity at 500 millibars varies between 5 per cent to supersaturation beyond 100 per cent for about 3 per cent of the processed spectra. Ammonia appears depleted over belts and relatively enhanced over zones. Local variations of ammonia, arguably associated with local dynamics, are found to occur in several locations on the planet (Oval BA, South Equatorial Belt). Cloud altitude, defined as the level where aerosol opacity reaches unit value at 3650 cm −1 (2.74 μ m), is maximum over the Great Red Spot (>20 km above the 1 bar level) and the zones (15 km), while it decreases over the belts and towards higher latitudes. The aerosol opacity scale height suggests more compact clouds over zones and more diffuse clouds over belts. The integrated opacity of clouds above the 1.3-bar pressure level is found to be minimum in regions where thermal emission of the deeper atmosphere is maximum. The opacity of tropospheric haze above the 200-mbar level also increases over zones. Our results are consistent with a Hadley-type circulation scheme previously proposed in literature for belts and zones, with clear hemisphere asymmetries in cloud and haze.